Effectiveness of reducing corneal astigmatism after combined high-frequency LDV Z8 femtosecond laser-assisted phacoemulsification and arcuate keratotomy - Lin, Hung-Yuan; Chen, Shuan; Chuang, Ya-Jung; Zhang, Suhua; Chang, Steven Wei-Hsin; Lin, Pi-Jung; Zhang, Zhe (Frontiers in Cell and Developmental Biology, 2022)
Purpose: In this retrospective study, the efficacy of the FEMTO LDV Z8 Femtosecond Laser-Assisted Cataract Surgery (Femto Z8 FLACS) and the Femtosecond laser Arcuate Keratotomy (FSAK) in decreasing the corneal astigmatism was investigated. Methods: During FLACS, FSAK was positioned with the help of the FEMTO LDV Z8 laser at a diameter of 8.5 mm and an 80% depth. Before and 3 months after surgery, the astigmatism of the cornea was measured with the aid of Pentacam. The variables influencing the efficacy of FSAK were assessed using the multiple regression analysis technique. Vector analyses were carried out. To determine the net corneal alterations, the with-the-wound and against-the-wound variations were computed along the FSAKs’ meridian. Results: This study investigated 80 eyes from 62 participants. The average keratometric astigmatism value was 0.92 ± 0.44 diopters (D). The average keratometric astigmatism decreased to 0.61 ± 0.45 D 3 months following FSAK compared to preoperative corneal astigmatism (p < 0.05). Additionally, there was a considerable decline in the percentage of eyes with ±0.5 D and ±1.0 D astigmatism, which reduced 3 months after surgery by 58% and 85%, respectively (p < 0.05). Conclusion: The FEMTO LDV Z8 laser can create an effective and precise arcuate keratotomy with an excellent safety profile, rapid recovery, and vision stability.